Disruption of estrogen signaling by developmental exposure to BPA and TBT causes long term functional deficits in zebrafish retina - Jensen, J. S.; Ouellette, L.; Harris, R.; Owrang, P.; Connaughton, V. P. (Frontiers in Pharmacology, 2026)
Bisphenol A (BPA) and tributyltin (TBT) are two endocrine disrupting compounds (EDC) that have opposite effects on estrogen signaling. BPA is an estrogen agonist that binds to all estrogen receptor types. TBT is an aromatase inhibitor that binds to the enzyme aromatase, preventing the synthesis of estrogen from testosterone. Both estrogen receptors and aromatase are localized to the retina and estrogen signaling is required for proper eye and retinal neurogenesis. Abnormal eye growth and retinal changes are reported immediately after developmental exposure to either EDC consistent with the role of estrogen in proper neurogenesis. In this review, we examine the impact of BPA and TBT exposure on the development and function of the visual system. We focus primarily on zebrafish but include data from other species to show trends across vertebrates. We discuss a case study designed to determine if a transient developmental exposure to BPA or TBT has persistent effects that are evident in adults and if these latent outcomes reflect the opposite impact of these compounds on estrogen signaling. Surprisingly, although some opposing outcomes were observed, most differences in adult retinal function were similar between the two compounds, with varying effects noted by concentration and exposure age. Overall, we conclude that developing zebrafish retina is sensitive to EDCs that target estrogenic pathways. However, these findings cannot be explained by estrogenic modulation alone, suggesting additional mechanisms beyond their current established roles.